METACOGNITIVE STRATEGY TRAINING IN THE TEACHING OF READING COMPREHENSION: IS IT EFFECTIVE IN EFL CLASSROOM? - ANITA DWI HAPSARI (Language-Edu, 2020)
Reading can be described as a communicating and active process, and a meaning-construction actions. This study purposes at examining the effectiveness of metacognitive strategy training in teaching reading comprehension of English Language Education Department student of UNISDA Lamongan in 2018/2019 academic year. This present study elaborates Experimental Research as its research design, particularly Randomized Matched Subjects Pre-Test Post-Test Design. Metacognitive strategy training that is implemented in this study consist of planning, monitoring, and evaluation strategy. In term of reading comprehension performance, the researcher focuses on reading comprehension on English Proficiency Test (EPT/TOEFL® like). Based on the outcome of the calculation of Paired Sample T-test, the mean difference of Experimental group and Control group was 3.9. Meanwhile, the output of Paired Sample Correlations show the large correlation between samples, where can see numeral both correlations are 0.848 and numeral of significance was 0.000 with t value is 2.960. Then, the Significance (2-tailed) 0.008 was lower than 0.05. It means that the difference among students’ score who are taught by metacognitive strategies and students’ score who are taught by conventional learning was significant. In brief, metacognitive strategies instruction is one of possible teaching strategy which is significantly be able to be applied to develop the students’ reading comprehension.